Coleridge and Communication - Bewell, Alan (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2012)
Although much has been written about Coleridge’s ideas concerning language, less has been said about the role that communication plays in his work, particularly his use of language as a medium for bridging the distance between himself and others. Coleridge felt that great poetry could successfully overcome this gap, and in his poetry there are moments when he felt that he was fully tuned-in to an intelligible universe created by an all-loving and all-communicating God. Such moments, when the “One Life” was revealed to him were based upon a theory of communication in which the universe was the medium of divine communication. More frequently, however, Coleridge was troubled by bad reception, by what he understood to be a failure of communication, times when he was denied complete participation in a fully intelligible world and when the gap separating himself from others and from nature appeared as a chasm. “Sometimes when I earnestly look at a beautiful Object or Landscape,” he writes in a notebook, “it seems as if I were on the brink of a Fruition still denied--as if Vision were an appetite: even as a man would feel, who having put forth all his muscular strength in an act of prosilience, at that very moment held back -- he leaps & yet moves not from his place” (Notebooks III, no 3767). At such times, Coleridge felt “held back,” wanting desperately to move forward from his sense of isolation but unable to do so. This state of tension, in the desire for complete communication in a context of communication breakdowns, characterizes Coleridge’s best writing. For Coleridge, poetry was the highest form of human communication, and the task of a poet was to use language to move his readers beyond the need for words. When communication failed, he felt that he was a failed poet. This essay will examine Coleridge’s commitment to the idea of perfect communication at the same time as it suggests that one aspect of Coleridge’s strength as a writer lies in those moments when he grappled with the fallibility of human communication and sought to build community in a world in which our relationship to others also includes isolation, misdirection, darkness, strangeness, and ghosts.